Varieties of English : a typological approach - Siemund, Peter, 1965- (Cambridge : Cambridge University Press, 2013)
'English is a highly diversified language that appears in a multitude of different varieties across the globe. These varieties may differ extensively in their structural properties. This coursebook is an introduction to the fascinating range of regional and social varieties encountered around the world. Comparing grammatical phenomena, the book analyses the varieties in depth, identifying patterns and limits of variation, and providing clear explanations. Using comparisons with other languages, the book identifies universal as well as language-specific aspects of variation in English. This book is specially designed to meet the needs of students, each chapter contains useful exercises targeted at three different ability levels and succinct summaries and practical lists of key words help students to review and identify important facts.'--Publisher's website.
Introduction -- Reflexivity and reflexive marking -- Pronominal gender -- Pronominal case -- Determiners -- Tense marking -- Aspect marking -- Modal verbs -- Negation -- Subject-verb agreement -- Ditransitive constructions -- Interrogative constructions -- The formation of relative clauses -- Summary and outlook.
Includes bibliographical references (pages 291-294) and indexes.
Includes index and references : p. 291-294.
Keywords: English language -- Variation -- Textbooks; English language -- Dialects -- English-speaking countries -- Textbooks